THE EFFECTS OF VOCABULARY AND GRAMMAR MASTERY ON STUDENTS’ WRITING SKILL IN RECOUNT TEXT - Jamhuri Jamhuri; Mashadi Said (INFERENCE: Journal of English Language Teaching, 2021)
Abstract: The research was performed in 9th-grade students of three (3) Private Junior High Schools in South Tangerang City. The method is an explanatory survey with quantitative research through the descriptive method, a method designed to determine if two or more variables are connected. The hypothesis test showed: 1) There are significant effects of vocabulary and grammar mastery jointly towards students’ writing skill in recount text at Private Junior High School in South Tangerang City. It is proved by the Sig = 0.000 < 0.005 and Fo = 57.783. The increasing vocabulary mastery contributes 0.395, and grammar mastery contributes to the contribution 0.240 towards writing skill in recount text. 2) There is a significant effect of vocabulary mastery towards students’ writing skills in recount text at Private Junior High School in South Tangerang City. It is proved by Sig = 0.000 < 0.005 and to 5.169. 3) There is a significant effect of grammar mastery towards students’ writing skills in recount text at Private Junior High School in South Tangerang City. It is proved by Sig = 0.00 < 0.05 and to 4.045 this second independent variable (X2.)Keywords: writing skills, recount text, vocabulary, grammar